Implementasi Strategi Komunikasi Digital Berbasis IMC pada Perusahaan Penempatan Pekerja Migran - Athaya Almira Nur Azzahra (Lembaga Pengembangan Kinerja Dosen, 2026)
Digital transformation in labor migration services in Indonesia is increasingly urgent as the reliance on digital platforms for communication, recruitment, and promotion increases. This study aims to examine the digital communication strategies implemented by the Indonesian Migrant Worker Placement Company (P3MI), with a focus on ethical practices, integrated marketing communication (IMC), as well as opportunities for future strategy development. The approach used is qualitative descriptive through literature study and participatory observation of PT Mitra Sinergi Sukses (MSS), a licensed P3MI that actively utilizes Instagram and official websites to reach prospective migrant workers. The results of the study show four main findings. First, although MSS displays visual consistency in digital branding, its communication strategy has not been integrated across platforms, thus weakening IMC's effectiveness. Second, the level of audience engagement is relatively low, characterized by a lack of interaction and the absence of two-way dialogue on social media. Third, from the aspect of communication ethics, weaknesses were found in the delivery of information, especially the promotion of successful migration without transparency regarding procedures and risks, as well as the use of personal data without adequate explanation or consent. Fourth, although the website provides a destination country-based registration form, there is no structured Customer Relationship Management (CRM) system or audience segmentation strategy. On the other hand, this study identifies significant opportunities for MSS to strengthen its digital presence through the use of artificial intelligence (AI) to increase audience engagement, CRM implementation, and the development of storytelling based on the diaspora community. This study concludes that the shift from one-way promotional communication to ethical, integrated, and data-driven strategies is an essential step in the empowerment of prospective migrant workers and the protection of the global workforce.